Selected Decisions and Selected Documents of the International Monetary Fund, 42nd Issue. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2022)
This volume documents decisions, interpretations, and resolutions of the Executive Board and Board of Governors of the International Monetary Fund, as well as documents relating to the United Nations and other international organizations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; SELD